Ki Hadjar Dewantara Educational Thought Perspective of Islamic Education - *, Muthoifin (Proceeding of International Conference on Teacher Training and Education, 2016)
Education is the guidance in the growth of childrens lives so that they can achieve salvation and happiness. Education must have a vision and noble mission; the vision is far into the future beyond time and space, while the mission of Islamic education is on accordance to the concept of Tawheed, so that it will always relevant in every time and all conditions. Education should be based on divine revelation (al-Quran and al-Hadith). If education is not guided and does not display the spirit of the two ideologies, the education can be mentioned as a strange education. The focus of this research is the profile of Ki Hadjar Dewantara, his educational thought based on the perspective of Islamic education review, the research is focused on the aspects of the conception of education issues, including: basic, content and education systems. The results of the study are: (1) the concept of education Ki Hadjar focused on aspects of guidance to children in order to achieve happiness based on the nature of nature. This is not consistent with the concept of Islamic education that focused on aspects of worship and Tawheed based on divine revelation; (2) Ki Hadjarâs basic education is the principle Pancadarma (five principles), which of the five principle is explicitly no principle of divinity, it is contrary to basic Islamic education which is based on al-Quran and al-Sunnah; (3) the Content or the essence of Ki Hadjarâs education is character, humanism, freedom, natural culture. In addition, It is incompatible with the core content of Islamic education Faith-monotheism, worship and noble character divine revelation (4) Ki Hadjarâs education system, good goals, curriculum, methods, teachers, students and the evaluation does not lead and is tied to the value of faith and worship. Moreover, it is not in line with the Islamic education system which has always associate with both religious values.